2014
DOI: 10.3389/fnana.2014.00042
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of adeno-associated virus serotype 9 (AAV9) vector after intrathecal and intravenous delivery in mouse

Abstract: Adeno-associated virus serotype 9 (AAV9)-mediated gene transfer has been reported in central nervous system (CNS) and peripheral tissues. The current study compared the pattern of expression of Green Fluorescent Protein (GFP) across the mouse CNS and selected peripheral tissues after intrathecal (i.t.) or intravenous (i.v.) delivery of equivalent doses of single-stranded AAV9 vector. After i.t. delivery, GFP immunoreactivity (-ir) was observed in spinal neurons, primary afferent fibers and corresponding primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
138
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(153 citation statements)
references
References 44 publications
10
138
4
1
Order By: Relevance
“…16,41 Although it is recognized that GAA expressed from the desmin promoter would similarly be unable to cross the blood-brain barrier, evidence of crossing the blood-brain barrier by AAV9 would confer cell autonomous correction of the CNS. 59,76 Building on success with AAV9-DES-GAA to attenuate functional decline of cardiac, respiratory, and skeletal muscle pathology in Pompe disease, we have applied a new paradigm to address both the immunological and neuromuscular complications using a copackaged, dual-AAV9 vector system that addresses the multisystem disease progression simultaneous with overcoming immune-related complications, which is likely to have the most persistent therapeutic benefit and increase survival rates. 11,37,46,47 The induction of immune tolerance enhances the success of gene therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,41 Although it is recognized that GAA expressed from the desmin promoter would similarly be unable to cross the blood-brain barrier, evidence of crossing the blood-brain barrier by AAV9 would confer cell autonomous correction of the CNS. 59,76 Building on success with AAV9-DES-GAA to attenuate functional decline of cardiac, respiratory, and skeletal muscle pathology in Pompe disease, we have applied a new paradigm to address both the immunological and neuromuscular complications using a copackaged, dual-AAV9 vector system that addresses the multisystem disease progression simultaneous with overcoming immune-related complications, which is likely to have the most persistent therapeutic benefit and increase survival rates. 11,37,46,47 The induction of immune tolerance enhances the success of gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…AAV8 was selected because of its natural propensity to target the liver and increase levels of T regs , and AAV9 was chosen because of its widespread transduction profile. 24,30,59,60 Gaa -/-mice (4-6 weeks old; n = 4/group) received AAV-GAA at two IV doses: 0.5 · 10 12 (low dose) or 5 · 10 12 (high dose) vg/kg of AAV8-or AAV9-LSPcoGAA and compared with lactated Ringer's solution (vehicle). At 8 weeks post-gene transfer, hepatic GAA activity was evaluated and showed a dosedependent response compared with vehicle-injected mice: 133 -32% of wild type in low dose AAV8-LSPcoGAA, 509 -10% of wild type in high dose AAV8-LSP-coGAA, 56 -26% of wild type in low-dose AAV9-LSP-coGAA, and 312 -25% of wild type in high-dose AAV9-LSP-coGAA ( p < 0.01; Fig.…”
Section: Aav9-lsp-cogaa Selectively Expresses In the Liver After Intrmentioning
confidence: 99%
“…12 It should be noted that the systemic distribution of intravenously injected AAV is not limited to the ENS. 4,5,13 In the light of gene therapy, future efforts should evaluate specificity-enhancing strategies such as ENS-specific promotors, AAV with modified glycan binding ability or micro-RNAs. 14,15 Enteric glia lacked transgene expression, but these cells could be targeted with other AAV serotypes or GFAP promotor-driven constructs, as these strategies have been proven successful in earlier work.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Recombinant adenoassociated viruses vectors (AAVs) belong to the most promising candidate vector systems in gene therapy and preclinical research 1,3 , but hitherto little is known about the transduction efficiency of the ENS by AAV. Rahim et al 4 and Schuster et al 5 have preliminarily indicated transduction of the myenteric plexus of the mouse with AAV9, and a more recent paper by Gombash et al 6 has detailed myenteric plexus transduction by self-complementary AAV9 in neonate and juvenile mice with green fluorescent protein (GFP) being expressed under a chicken-b-actin/cytomegalovirus (CB) hybrid promoter. However, data on submucosal plexus transduction are currently lacking, as is quantification of the neuronal subtypes transduced by AAV.…”
mentioning
confidence: 99%
“…For instance, Shuster et al [133] observed comparable levels of peripheral transduction using IV and intrathecal injections, suggesting that a fraction of IT delivered vector is moved from the subarachnoid space to systemic circulation. Moreover, according to Samaranch et al.…”
Section: Intravascular Versus Intrathecal Administrationmentioning
confidence: 95%